Arabic Language Use And Islamic Education In Teaching Value To Graduates In Saudi Universities - Faisal Bin Shabib Mosleet Alsubaie (Ijaz Arabi Journal of Arabic Learning, 2022)
Numerous studies have been conducted to ascertain the value of the Arabic language to various aspects of Islamic studies. Arabic, along with other tongues, can be used as a mode of communication to spread awareness about Syariah. The fact that the Holy Quran and Sunnah, which are considered essential texts in Islam, are written in Arabic is mostly to blame for this. The purpose of this study is to evaluate the impact of the use of Arabic in Islamic Education on the maturation of individuals who graduated from an Arabic-language institution in Saudi Arabia to inculcate values in students. Participating in this research are students from the College of Science and Humanities at Sulail. They are pursuing degrees in either the Bachelor of Arabic language or the Bachelor of Islamic Studies programs. A survey was carried out to investigate whether or not there is a connection between students' levels of Arabic language competency and how they learn from the classes in which they are enrolled. The purpose of the survey is also to find out how students feel about the usefulness of courses in Arabic language use in Islamic studies and its positive impact on value enhancement. The vast majority of people who participated in the survey believe that learning Arabic and Islamic Studies is necessary for students' overall growth and development.